Mesjański ekosystem (Iz 11,6-8) - Sobierajski, Bartłomiej (Verbum Vitae, 2017)
Our understanding of any natural ecosystem includes not only a description of the species of plants and animals it encompasses, but also an analysis of the relationships involved, both between the species themselves and between each of them and their environment. The article attempts to answer such questions about the nature of the messianic peace outlined in Isa 11:6-8, an investigation based mainly on the activities and behaviors characteristic of the animals and human figures seen in this passage. Such an approach to the subject complements much previous scholarship, which includes numerous detailed analyses of the species named in Isa 11:6-8, as well as attempts to interpret their meaning. According to Isaiah, peace is not simply the absence of conflict but also involves the harmonious coexistence and cohabitation of people. Still further, it always includes the idea of living in abundance under the dominion of a righteous ruler. This understanding of peace can be seen in various other parts of Proto-Isaiah, especially in Chapter 32.